Magnetospheric Multiscale Dayside Reconnection Electron Diffusion Region Events. Issue 6 (20th June 2018) - Webster, J. M.; Burch, J. L.; Reiff, P. H.; Daou, A. G.; Genestreti, K. J.; Graham, D. B.; Torbert, R. B.; Ergun, R. E.; Sazykin, S. Y.; Marshall, A.; Allen, R. C.; Chen, L.‐J.; et al.
Abstract: We use high‐resolution data from dayside passes of the Magnetospheric Multiscale (MMS) mission to create for the first time a comprehensive listing of encounters with the electron diffusion region (EDR), as evidenced by electron agyrotropy, ion jet reversals, andj E ′ > 0. We present an overview of these 32 EDR or near‐EDR events, which demonstrate a wide variety of observed plasma behavior inside and surrounding the reconnection site. We analyze in detail three of the 21 new EDR encounters, which occurred within a 1‐min‐long interval on 23 November 2016. The three events, which resulted from a relatively low and oscillating magnetopause velocity, exhibited large electric fields (up to 100 mV/m), crescent‐shaped electron velocity phase space densities, large currents (≥2 μA/m 2 ), and Ohmic heating of the plasma ( 10 nW/m 3 ). We include an Ohm's law analysis, in which we show that the divergence of the electron pressure term usually dominates the nonideal terms and is much more turbulent on the magnetosphere versus the magnetosheath side of the EDR. Plain Language Summary: NASA's Magnetospheric Multiscale (MMS) mission was designed to study magnetic reconnection, a process in which oppositely directed magnetic fields embedded within two neighboring plasma populations annihilate, dumping magnetic energy into the plasmas. Previous missions studying reconnection in space were not fully equipped to analyze how the electrons in the plasma behave near the core of a reconnection site. This study provides MMS researchers with many new reconnection events to dissect, and calls special attention to three events that occurred back to back. Each event included is very unique and helps to fill in another piece of the reconnection puzzle. Perhaps the ultimate goal of these studies is to provide insight into methods of shutting down the reconnection process, which is known to impede attempts toward a stable nuclear fusion engine. A blueprint for stable nuclear fusion could solve mankind's energy needs forever. Key Points: MMS mapped the EDR and near‐EDR several times during a sequence of new dayside encounters Turbulence in Ohm's law terms is greatest on the magnetospheric‐side EDR, near the plane containing the X line and boundary normal vector Thirty‐two EDR or near‐EDR encounters show crescent‐like enhancements in electron velocity space perpendicular to the local magnetic field